At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals.

Solve for X
3ax/5 - 4c = ax/5


Sagot :

[tex]\frac { 3ax }{ 5 } -4c=\frac { ax }{ 5 } [/tex]
First multiply both sides by 5:
[tex]5\cdot (\frac { 3ax }{ 5 } -4c)=5\cdot \frac { ax }{ 5 } \\ 3ax-20c=ax[/tex]
then take the ax to the other side :
[tex]3ax-20-ax=0[/tex] and simplify:
[tex]2ax-20c=0[/tex] factor:
[tex]2(ax-10c)=0\\ ax-10c=0\\ ax=10c\\ x=\frac { 10c }{ a } [/tex]